2010
DOI: 10.2174/1875397301004010001
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Cell-Based High-Throughput Assay to Screen for Inhibitors of Organic Anion Transporting Polypeptides 1B1 and 1B3

Abstract: The two organic anion transporting polypeptides (OATPs) 1B1 and 1B3 are expressed at the sinusoidal membrane of hepatocytes. They have a broad and overlapping substrate specificity and transport many endobiotics and drugs. Specific inhibitors are required to determine the contribution of each OATP to the hepatocellular uptake of common substrates. We have developed a cell-based high-throughput assay to screen chemical libraries in order to identify such inhibitors for OATP1B1 and OATP1B3. We have used OATP1B1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
92
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 27 publications
12
92
1
Order By: Relevance
“…This K m is in the range of the mean plasma concentration in patients (0.85 ± 0.21 µM) after 24 h of infusion [41]. Our conclusion that paclitaxel could be a better substrate for OATP1B1than OATP1B3 is supported by very recent experiments of Gui and coworkers as they found that paclitaxel (2.5 µM) inhibited the uptake of the OATP1B1/1B3 substrate fluorescein-methotrexate by 93% in OATB1B1-but only by 53% in OATP1B3-expressing CHO cells [42]. Differences in estrogen-responsive and estrogen-independent ovarian cancer cell lines also suggest that alterations in mRNA expression levels may also be observed in tumor tissue samples from patients.…”
Section: Discussionsupporting
confidence: 77%
“…This K m is in the range of the mean plasma concentration in patients (0.85 ± 0.21 µM) after 24 h of infusion [41]. Our conclusion that paclitaxel could be a better substrate for OATP1B1than OATP1B3 is supported by very recent experiments of Gui and coworkers as they found that paclitaxel (2.5 µM) inhibited the uptake of the OATP1B1/1B3 substrate fluorescein-methotrexate by 93% in OATB1B1-but only by 53% in OATP1B3-expressing CHO cells [42]. Differences in estrogen-responsive and estrogen-independent ovarian cancer cell lines also suggest that alterations in mRNA expression levels may also be observed in tumor tissue samples from patients.…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with this, our recent studies (63) using estrone sulfate and estropipate, potent prototypical inhibitors for OATP1B1 (66), also yielded different IC 50 values for the uptake of pitavastatin (IC 50 , 0.6 and 0.8 μM, respectively) as compared to that of atorvastatin (IC 50 >50, >10 μM, respectively). Further complicating this is the fact that currently we have little understanding of the kinetics of drug-transporter interactions.…”
Section: Transporter Data Are Dependent On In Vitro Model Systems Andsupporting
confidence: 83%
“…Distribution ratios (i.e., the ratio of intracellular concentration of radiolabel relative to the extracellular concentration) were calculated as described previously (14). IC 50 s were calculated using nonlinear regression analysis and are tabulated in Table 2.…”
Section: Fig 4 Uptake Of [mentioning
confidence: 99%
“…Current assays for transporter inhibition in a high-throughput format generally employ radiolabeled substrate or cell death of a transporter-overexpressing cell line as a readout (13,14). Both formats have significant limitations.…”
mentioning
confidence: 99%